2017
DOI: 10.1111/micc.12380
|View full text |Cite
|
Sign up to set email alerts
|

Roles of NADPH oxidase and mitochondria in flow‐induced vasodilation of human adipose arterioles: ROS‐induced ROS release in coronary artery disease

Abstract: Objectives Hydrogen peroxide (H2O2) contributes to flow-induced dilation (FID) of human arterioles. This study is designed to examine the roles of mitochondria and NADPH oxidase in modulating the release of ROS and in mediating FID. We tested whether NADPH oxidase contributes to mitochondrial ROS generation in arterioles during coronary artery disease (CAD). Methods Visceral adipose arterioles obtained from patients with or without CAD were cannulated and pressurized for videomicroscopic measurement of arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Briefly, mesenteric resistance arteries are cannulated on glass micropipettes and pressurized for 1 hour by gravity‐induced pressure (60 cm H 2 O) from solution‐filled reservoirs that perfuse the artery. Arteries are then preconstricted with endothelin‐1 and increasing levels of intraluminal flow administered by moving reservoirs in equal and opposite directions, thus maintaining intraluminal pressure while flow through the vessel increases . No differences are observed between baseline arterial diameters when comparing relevant experimental groups (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, mesenteric resistance arteries are cannulated on glass micropipettes and pressurized for 1 hour by gravity‐induced pressure (60 cm H 2 O) from solution‐filled reservoirs that perfuse the artery. Arteries are then preconstricted with endothelin‐1 and increasing levels of intraluminal flow administered by moving reservoirs in equal and opposite directions, thus maintaining intraluminal pressure while flow through the vessel increases . No differences are observed between baseline arterial diameters when comparing relevant experimental groups (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Dilations to flow were measured as previously described . First‐order mesenteric arteries were cannulated and equilibrated at 60 cm H 2 O for 1 hour in a chamber designed to accept external bath circulated by a peristaltic pump.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some settings, NOX is the source of LPA‐stimulated ROS (Lin et al ., ). We cannot exclude a role for NOX in FID following LPA treatment, which could occur via ROS‐induced ROS release where small amounts of NOX‐related ROS stimulate release of mitochondrial ROS or vice versa (Zinkevich and Gutterman, ; Zinkevich et al ., ). In fact, a recent study showed LPA 1 and LPA 3 receptor‐dependent activation of PLC, PKC and eventual stimulation of NOX to generate ROS in cell culture model (Lin et al ., ).…”
Section: Discussionmentioning
confidence: 97%